PENELITIAN TINDAKAN KELAS DALAM PEMBELAJARAN BAHASA INGGRIS DI KELAS VIII SMP NEGERI 4 KOTANOPAN DENGAN MENGGUNAKAN FLASH CARD - Sari, Leli Purnama (CV. Alfa Pustaka, 2024)
This study aims to improve the English skills of grade VIII students at SMP Negeri 4 Kotanopan through the application of the Flash Card learning method. This research uses the Classroom Action Research Method (PTK) which is carried out in three cycles, each consisting of four stages: planning, implementation, observation, and reflection. The results showed that the use of flash cards effectively improved students' skills in mastering English vocabulary, with the completion rate increasing from 60% in the first cycle to 85% in the third cycle. This study shows that the flash card method can significantly improve the English learning process.